Workable Environmentally Related Energy Taxes - Fernando Navajas; Monica Panadeiros; Oscar Natale (Inter-American Development Bank (IDB), 2012)
This paper models an energy tax reform process out of a status quo and towards environmentally related excises, distinguishing between uniform and non-uniform tax components, positive and normative tax structures, and adopting a non- Ramsey specification. The model is implemented for Argentina, Bolivia and Uruguay, and a rebalancing of fuel taxes is found where gasoline and diesel are the main drivers, due in part to higher estimates of the environmental costs of diesel relative to gasoline than those found in Parry and Strand (2010) for Chile. Environmental (mostly local) gains of the reform are significant, while fiscal impacts are positive and large. They do not, however, include double dividend effects because of price increases in widespread energy inputs triggered by the reform exercise. The tax reform has a positive distributive impact in Uruguay, while large pre-existing price distortions tend to produce negative impacts in Argentina and Bolivia.
Keywords: H23; Q40; Q51; 330